Pengalaman Belajar Mahasiswa Terkait Peran Skenario dalam Tutorial - Nindya Aryanty; Gandes Retno Rahayu; Efrayim Suryadi (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2013)
Background: Tutorial in Problem-based Learning is a learning method where faculty prepares a scenario to trigger students learning through small group discussion. In the first meeting of tutorial, a group of students analyze the scenario given by raising and answering questions to explore phenomenon described in the scenario. Unresolved questions then become students’ learning issues which are a starting point for their independent learning. Answers gathered during individual learning then being reported and synthesized on the second meeting. The aim of this study is to investigate student learning experience regarding the role of scenario in tutorial.Method: Reflective writings of 36 medical students about learning experience using PBL collected at the end of first year were analyzed qualitatively through within-case analysis and cross-case analysis. Methods chosen to increase credibility are peer review and verbatim.Results: Students found that some scenarios stimulated their learning since it increase students’ curiosity. Scenarios discussing the latest news in medicine also attract to students to learn more. However, majority students admitted that some scenarios not providing enough clues to guide student determining learning objectives. Student preferred to discuss and formulate learning objectives by listing the title/topic of lecture scheduled on the same week as related tutorial session. Scenario that found identical to scenario given on the previous academic year also demotivates students to learn deeply. Students admitted learning from their senior notes in preference to learning from other valid resources. In addition, this study found that scenarios that lead students to discuss topic beyond their first-year competencies also disencourage students learning.Conclusion: Scenario plays an important role in student learning. Therefore, scenario have to be carefully designed by determining students’ prior knowledge, the length of independent learning session needed and learning resources available for students. It is also necessary to always renew the scenario for every academic year and improve its quality, for example by adding visual trigger along with written text.